KONSERVASI TEBING SUNGAI MELALUI EDUKASI PENCEGAH EROSI DI DESA KALEBENTANG KABUPATEN TAKALAR - Virlayani, Asnita; Pertiwi, Nurlita (UNM Environmental Journals, 2023)
This study aims to determine how much knowledge the community has about erosion on the banks of the river and how the attitude of the people of Kale Bentang Village, Takalar Regency, is in preventing erosion. Data collection was carried out by 20 people. Educating the public about riverbank conservation to prevent erosion is the main objective of this research. Quantitative method in data collection using structured interviews then performed analysis with proportion techniques, then data collection using a questionnaire technique. As a result, there has been an increase in the knowledge and attitudes of the people who previously did not know about the dangers of erosion, now they know and are enthusiastic about preserving the plants on the riverbanks